Harnessing E-Collaboration for Rural Tourism Recovery after COVID-19: Dual Analysis using SWOT and Porter’s Diamond Model - Mardiana Purwaningsih; Betty Purwandari; Fathia Prinastiti Sunarso; Farisya Setiadi (Emerging Science Journal, 2021)
IT for rural tourism was in place before the COVID-19 pandemic emerged; however, the initiatives were intermittent and isolated. The effects of the pandemic encourage e-collaboration to accelerate the recovery of tourism. This study explores the opportunities, strategies and barriers to e-collaboration in tourism business activities. Systematic literature studies were carried out by the PRISMA approach and analyzed with the fuzzy Delphi method (FDM). Meta-analysis results are mapped in a matrix combination of SWOT and Porter’s Diamond Model. This matrix was discussed with experts selected based on their experience in IT-based collaborative activities through FDG. This study’s driving factors are management commitment, culture, trust, citizens, and local community involvement. Inhibiting factors are a lack of IT, the risk of conflict, and particular parties’ domination. Several strategies to increase e-collaboration opportunities are empowering local entrepreneurship, encouraging continuous innovation, and sharing knowledge. Conflict management and increasing trust between members need to be considered to overcome barriers to e-collaboration. This study provides a novel overview of the main issues discussed in previous tourism research regarding the importance of IT to accelerate economic recovery in the face of disruption, such as a pandemic. The study examines the case of Indonesia and hopes to become a reference for optimizing IT for the recovery of rural tourism in developing countries with similar characteristics. Doi: 10.28991/esj-2021-01297 Full Text: PDF